An overview of forecasting facing breaks - Castle, J; Clements, M; Hendry, D (Springer Verlag, 2016)
Economic forecasting may go badly awry when there are structural breaks, such that the relationships between variables that held in the past are a poor basis for making predictions about the future. We review a body of research that seeks to provide viable strategies for economic forecasting when past relationships can no longer be relied upon. We explain why model mis-specification by itself rarely causes forecast failure, but why structural breaks, especially location shifts, do. That serves to motivate possible approaches to avoiding systematic forecast failure, illustrated by forecasts for UK GDP growth and unemployment over the recent recession.